PENINGKATAN KUALITAS PENGENCERAN DAN LAMA PENYIMPANAN SEMEN AYAM KAMPUNG MELALUI PENAMBAHAN YOLK PUYUH (Conturnix conturnix japonica) - Wajo, M Jen; M, Jhoni; Abdilla, . (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2006)
The aimed of experiment was to increace the quality of kampong cock's cement by adding quail's yolk (yolk of Conturnix conturnix japonica) in Ringger's solution. The experiment was conducted at Laboratorium of animal production by collection cement of 10 adul kampong cocks. Moreover the macroscopic and microscopic observation was carried out to observe the quality of fresh cock's cement the fresh cement was then diluted by quail's yolk and Ringer's solution, and was stored at 5 0c. Results of research showed that the percentage of quail's yolk had a significant effect on storage time duration. Dilution in 20 % quail's yolk stored at 24 hours gave the best result. However dilution in 30 % quail's yolk in 24 hours storage time was still aplicable for AI.